IMPLEMENTATION AND SIGN TEST ANALYSIS FOR MEASURING AR EFFECTIVENESS AS PROMOTION TOOL - Deny Jollyta; Muhammad Siddik; Lasman Toni (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2018)
Many smartphone entrepreneurs compete to promote various brands of smartphones. Conventional promotion systems become a mainstay for almost all smartphone entrepreneurs. As a result, sales turnover tends to decrease because it promotes the same goods in the same way. This research helps improve the promotion system peacefully using technology that can be run through the smartphone itself. Augmented Reality (AR) is technology that is the view of the physical world collaborated between reality and 3D virtual image. AR technology is designed on smartphone models to be an application running on the android platform and built on the Unity 3D program. The AR app will be tested on an android device with 3 different versions using Black Box testing. In addition, AR impact analysis is done on smartphone sales to see the response of potential customers to promotion system. The analysis is done by Sign Test method. Over all, the results of this study indicate that the application of AR is successfully tested on all versions of android and the analysis of this impact by Sign Test is good enough to smartphone entrepreneurs promotion system and get a pretty good response from prospective customers.